2014
DOI: 10.1155/2014/803783
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Catalyst-Free Esterification of Oleic Acid in Compressed Ethanol

Abstract: The esterification of oleic acid in a continuous catalyst-free process using compressed ethanol was investigated in the present study. Experiments were performed in a tubular reactor and variables investigated were temperature, pressure, and oleic acid to ethanol molar ratio for different residence time. Results demonstrated that temperature, in the range of 473 K to 573 K, and pressure had a positive effect on fatty acid ethyl esters (FAEE) production. In the experimental range investigated, high conversions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
3
12
0
4
Order By: Relevance
“…The FFA content was determined by the Ca 5a-40 method (AOCS, 1998) and FFA conversion was calculated based on the content of free fatty acids in the oil and in samples of the reaction medium, as reported by Abdala et al (2014a). Table 3 presents the matrix of the Plackett and Burman design with 12 assays (PB-12), with coded values for the independent (factors) variables: temperature, pressure, MPO to ethanol mass ratio, water and co-solvent addition, with the response in terms of FAEE yield and FFA conversion.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FFA content was determined by the Ca 5a-40 method (AOCS, 1998) and FFA conversion was calculated based on the content of free fatty acids in the oil and in samples of the reaction medium, as reported by Abdala et al (2014a). Table 3 presents the matrix of the Plackett and Burman design with 12 assays (PB-12), with coded values for the independent (factors) variables: temperature, pressure, MPO to ethanol mass ratio, water and co-solvent addition, with the response in terms of FAEE yield and FFA conversion.…”
Section: Methodsmentioning
confidence: 99%
“…Abdala et al (2014a) reported high conversion of oleic acid, i.e. 70%, in the reaction with ethanol at 20 MPa, with 1:1 oleic acid to ethanol mass ratio and 10 minutes at 473 K; this conversion increased to 88% at 573 K.…”
Section: Effect Of Temperaturementioning
confidence: 97%
See 2 more Smart Citations
“…The acidity of this oil was 0.76%, humidity of 0.16% and phosphorus content of 77.86 ppm. The percentage of free fatty acid (acidity) was determined following the method used by Abdala et al [8], based on the AOCS Official Method Ca 5a-40, which uses an acid-base titration. The titrant is an ethanol solution of potassium hydroxide (KOH) previously standardized.…”
Section: Methodsmentioning
confidence: 99%